2013
DOI: 10.1021/pr4006734
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous N-Glycan Structures with an Internal Fucose Branched to GlcA and GlcN Residues Isolated from a Mollusk Shell-Forming Fluid

Abstract: This report describes the structural details of a unique N-linked valence epitope on the major protein within the extrapallial (EP) fluid of the mollusk, Mytilus edulis. Fluids from this area are considered to be responsible for shell expansion by a self-assembly process that provides an organic framework for the growth of CaCO3 crystals. Previous reports from our laboratories have described the purification and amino acid sequence of this EP protein which was found to be a glycoprotein (EPG) of approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…To locate the position of the fucosylation, the permethylated N-glycans from both forms were subjected to ESI-MS n fragmentation [15,16]. When the fucosylated composition (Hex3HexNAc2Fuc1) from the tetramer was analyzed, the fucose residue was found to be linked to the reducing end GlcNAc of the oligosaccharide Man3GlcNAc2Fuc1 (Supplemental Fig.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To locate the position of the fucosylation, the permethylated N-glycans from both forms were subjected to ESI-MS n fragmentation [15,16]. When the fucosylated composition (Hex3HexNAc2Fuc1) from the tetramer was analyzed, the fucose residue was found to be linked to the reducing end GlcNAc of the oligosaccharide Man3GlcNAc2Fuc1 (Supplemental Fig.1).…”
Section: Resultsmentioning
confidence: 99%
“…When required, N-glycans were further reduced to the corresponding alditols by the addition of 200 ÎŒL of NaBH 4 (10 mg/mL in 0.01M NaOH). The reduced N-glycans were purified using hand-packed cellulose cartridges [15] and permethylated [31] for MS n analysis.…”
Section: Methodsmentioning
confidence: 99%
“…EP is an acidic glycoprotein with a high histidine content that can bind Ca 2+ and heavy metals (Renwrantz et al ., ; Hattan et al ., ; Schneeweiss et al ., ; Yin et al ., ; Abebe et al ., ). Recently, by MS‐based approach, a complex and anomalous N‐glycan structure was determined in M. edulis EP (Zhou et al ., ). Such unique structure and calcium and heavy metal‐binding properties suggest a possible role of EP in multiple biological functions including shell formation, metal ion transportation and detoxification (Zhou et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent examples of such compounds discovered using MALDI techniques include the high‐mannose glycans from Chlamydomonas reinhardtii which contain one and two xylose residues and up to three methyl mannose units (Mathieu‐Rivet et al, ). Also, Zhou et al () have identified tetra‐antennary glycans with internal fucose residues containing 3‐linked GlcNAc and 4‐linked 4‐methylglycuronic acid in place of each galactose residue ( 75 , 76 , 77 ). In these structures and structures 78–81 , the logical symbols proposed by Harvey et al () rather than the internally inconsistent (as the authors admit) (Varki et al, ), but more commonly used symbols originally proposed by the Consortium for Functional Glycomics.…”
Section: Studies On Specific Carbohydrate Typesmentioning
confidence: 99%